National Intellectual Capital Disclosure of Emerging Country in Asia - Tasyahadul Fadlatil Laili; Ihyaul Ulum; Dwi Irawan (Faculty of Economics and Business Universitas Muhammadiyah Riau, 2022)
Intangible assets in the form of intellectual capital have been proven to be one of the factors that influence a company’s success. Previously the concept of intellectual capital was used in the focus of the company's scope, meanwhile theorists argued that the concept of intellectual capital could be incorporated into the state called National Intellectual Capital (NIC). Therefore, the purpose of this paper is to describe the NIC disclosures of each developing country in Asia. The results show that most developing countries in Asia have already disclosed their NICs. Afghanistan is a country that has a low NIC value. This is also in accordance with the financial capital rating as measured by GDP. However, countries with high GDP, including Qatar, United Arab Emirates, and Brunei Darussalam, are countries whose NIC scores are not so high. This is because the country has tangible assets of natural resources in the form of oil.